A colored Petri net model for DisCSP algorithms. (29th June 2017) - Pascal, Carlos; Panescu, Doru
Summary: The aim of this paper is to present a colored Petri net that models a system applying a DisCSP method. Our study considered 3 representative DisCSP algorithms: synchronous backtracking, asynchronous backtracking, and weak‐commitment search. To obtain the model, it was necessary to transpose the operation of a DisCSP‐based system into a discrete event system. The constructed colored Petri net is presented, with details on the information stored in places, procedures associated with transitions, and communication between agents. Through the performed trials (with the n‐queens problem), it was proved that the model is correct, easy to use, and adaptable to different operation conditions. The conducted simulations revealed new results about the way the 3 analyzed algorithms compare one with the other. It was showed that the performance of weak‐commitment search is degrading in cases close to real conditions, namely, when agents use un‐updated information about the state of system. We could also study 3 strategies for improving the performance of DisCSP algorithms, making them more practicable. The proposed model is available for open use, it is independent of the software that carries out a DisCSP method, and it can be enhanced for other DisCSP algorithms and diverse communication schemes.